The Efficiency of Producing Biodiesel from Used Cooking Oil by Precipitating Blood Cockles Shell Waste with a CaO Catalyst - Alif Julian Putra Rahmandika; Achmad Rahditya Viman Anggoro; M. Fikri; Rahmita Padmasari; Yusratus Sakinah; Ika Nawang Puspitawati (Nusantara Science and Technology Proceedings, 2023)
Bio-based waste materials perform an essential duty as valuable sources of components that can be effectively utilized as active phases in the synthesis of CaO catalysts for the generation of biodiesel. The abundance of shell Blood cockles is considerable. Additionally, Indonesia has a stockpile of used cooking oil. The utilized cooking oil has a notable concentration of fatty acids, presenting the potential for conversion into biodiesel. The technology of converting leftover cooking oil into biodiesel through transesterification has undergone significant advancements. An accelerator is necessary to boost the biodiesel yield to attain a sufficiently high yield. The CaO catalyst was selected due to its ability to expedite and boost biodiesel output. This study evaluated the blood clam shell's potential as a transesterification catalyst for used cooking oil. This study used temperature and concentration change variables for transesterification, with a settle variable of 60 minutes. The concentrations of the variables are 3 N, 4 N, 5 N, 6 N, and 7 N, whereas the temperatures are 45 ?C, 50 ?C, 55 ?C, 60 ?C, and 65 ?C. With varying transesterification times of 60 minutes, transesterification temperatures of 60°C and 65°C, and catalyst concentrations of 6N and 7N, the research findings indicate that utilizing this catalyst can boost biodiesel yield with conversion yields of 85%, 88%, and 95%. This demonstrates that temperature can also promote improving biodiesel production and that using catalysts can boost the conversion of biodiesel to over 90% or more.